Qualitative Study: Family Support for Post-Partum Mothers with HIV in Papua - Yustika Rahmawati Pratami; Wiwit Vitania; Hasnia Hasnia; Yuliandary Yunus (GLOBAL HEALTH SCIENCE GROUP, 2025)
The support that mothers with HIV expect is not only during pregnancy but also throughout the postpartum period and the rest of their life as a mother. Objective: to dig deeper into family support for postpartum mothers with HIV. This research is a quantitative research with a phenomenological approach. The number of participants in this study is two participants who will be interviewed in depth using an unstructured interview guide. Data analysis in this study is divided into three parts, including data reduction, data display and conclusion or verification. Family support is important for all informants, both support from parents and from husbands. Participants felt that the support they received from their families was much greater than the support they received from their husbands.